Stunted Children Has Higher Risk of Overweight: A Study on Children Aged 6-12 Years in Eight Provinces in Indonesia - Yasmin, Ghaida; Kustiyah, Lilik; Dwiriani, Cesilia Meti (Pakistan Journal of Nutrition, 2019)
Background and Objective: A higher risk of overweight has been widely described in other populations but very limited information was available on Indonesian school-aged children (ISC). The aim of this study was to analyze the association between stunting and overweight ISC. Materials and Methods: This study used electronic data of Basic Health Research (BHR) 2010 which was designed as a cross sectional survey. A total of 8,599 ISC aged 6-12 years from eight provinces in Indonesia were selected for the analysis. Overweight and obese were defined as body mass index (BMI) for age Z-score (BAZ) of ≥+1 and ≥+2 standard deviation (SD), while stunting was defined as a height-for-age Z-score (HAZ) of <-2 SD based on WHO cut-off point. Results: The prevalence of overweight, obesity and stunting in ISC were 19.5, 7.9 and 28.0%, respectively. There were 7.5% of ISC categorized as having concurrent stunting and overweight. Most of them were boys and at younger age. They also had low economic status, low parents education and lived in rural areas (p<0.05). In multivariate logistic regression analyses adjusted for all factors, stunting was associated with overweight (OR = 2.33, 95% CI: 2.06-2.61). Conclusion: It is apparent that there is a significant association between stunting and overweight in ISC. This association implies that the double-burden of malnutrition (DBM) does exist in Indonesia and comprehensive planning is needed to overcome the problem.